2020
DOI: 10.33225/jbse/20.19.842
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Students’ High-Order Cognitive Skills for Hierarchical Designs in Micro and Symbolic Particulate Nature of Matter

Abstract: To be familiar with micro and symbolic performances, students could work out more effective approaches of innovated techniques known as five hierarchical designs in chemistry equilibrium. However, the most frequently reported problem in students’ assessment of chemistry study is attributed to their poor skill recognizing basic concepts. The aim of this research was to construct the 6 test items to help undergraduate students assess their high-order and low-order cognitive skills as a deeper framework of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In addition to the finding by Jaber and BouJaoude (2012) for macro-micro-symbolic teaching in promoting students' latent conceptual understanding and relational learning of chemical reactions, the claims for thermodynamic properties by Becker et al (2013) served as an alternative justification of students' particulate-level of understanding physical and chemical properties. The improvement of Su's (2020) proposal for micro and symbolic performances also animated students' cognitive skills and advanced their hierarchical understanding in chemistry equilibrium classroom.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to the finding by Jaber and BouJaoude (2012) for macro-micro-symbolic teaching in promoting students' latent conceptual understanding and relational learning of chemical reactions, the claims for thermodynamic properties by Becker et al (2013) served as an alternative justification of students' particulate-level of understanding physical and chemical properties. The improvement of Su's (2020) proposal for micro and symbolic performances also animated students' cognitive skills and advanced their hierarchical understanding in chemistry equilibrium classroom.…”
Section: Discussionmentioning
confidence: 95%
“…Many instructors, science educators, and researchers have pointed out the subtle aspects of students' HOCSoriented development in chemistry education (Vachliotis et al, 2014;Su, 2017Su, , 2020. Essential learning objectives are needed for students to construct higher-order thinking abilities and problem-solving implements in chemistry equilibrium.…”
Section: Cognitive Levels Of Marzano's Taxonomymentioning
confidence: 99%
“…Student interview responses and teacher observations indicated that SSICM's use of argument in the classroom was a real benefit. SSICM's argumentation provided benefits, such as students' learning qualities in reading, writing, high order thinking, and problem-solving (Chin et al, 2016;Su, 2020Su, , 2016. From argument to science research, teachers found that students improved scientific knowledge to express the right ideas and positive argumentative attitude in class.…”
Section: Teacher and Students' Feedbackmentioning
confidence: 99%
“…Several studies on assessment especially on the development of HOTS-based instruments have been carried out (Rintayati, P, 2021;Su, 2020;Hidayat, 2020;Luo, 2020;Rahayu, 2020;Subia, G.S, 2020;Risna, 2020;Kurniawan, 2019 ;Istiyono, E, 2019;Semilarski, 2019;Wahono, 2019;Utomo, 2018;Hamdi, 2018;Kusuma, 2017;Ahmad, 2017;Kurbanoglu, 2017;Barz, 2017;Saat, 2016;Samritin, 2016;Hanum, 2015 ;Park, 2014;Muhammad, 2014;Lemons, 2013;Koksal, 2010). However, their study only focus on the development of diagnostic instruments, the introduction and development of the HOTS instruments in general to measure students' scientific reasoning skills to achieve the target scores of PISA and TIMSS international standards.…”
Section: Introductionmentioning
confidence: 99%